Solve for x:

\(x^2+10x+9=0\)

\(x^2+10x+9=0\)

Solve for x:

\(x^2+10x+9=0\)

\(x^2+10x+9=0\)

Detailed Explanation

Factor the quadratic equation: \(x^2+10x+9=0\)

\((x+1)(x+9)=0\)

For this expression to be true, the left side of the expression must equal zero. Therefore, either (x + 1) or (x + 9) must equal zero:

If (x + 1) = 0, x must equal -1

If (x + 9) = 0, x must equal -9

So the solution is that x = -1 or -9.

\((x+1)(x+9)=0\)

For this expression to be true, the left side of the expression must equal zero. Therefore, either (x + 1) or (x + 9) must equal zero:

If (x + 1) = 0, x must equal -1

If (x + 9) = 0, x must equal -9

So the solution is that x = -1 or -9.